On the issue of the “ecological corridor” concept - Jantassova, A.D. (Bulletin of the Karaganda University “Law Series”, 2023)
The following scientific paper explores the issue of defining the concept of ecological corridor as a means of protecting Special Protected Natural Areas (SPNA) and objects of the State Nature Reserve Fund (SNRF). The statutory definition given in Paragraph 22 of Article 1 of the Law of the Republic of Kazakhstan “On Special Protected Natural Areas” (hereinafter referred to as the SPNA Law) does not accurately reflect the essence and features of ecological corridors, or their main purpose. A number of legislative rules on environmental corridors contained in Article 81 of the SPNA Law and relevant resolutions of the Government of the Republic of Kazakhstan require adjustments as well. The paper gives a brief historical overview of the development of rules on ecological corridors within the environmental legislation of the Republic of Kazakhstan, as well as the process of establishing ecological corridors. The study has revealed very little attention paid both in Kazakhstan’s legislation and legal science to the definition of the concept of ecological corridor. Meanwhile internationally, based on the spatial culture model Patch-Corridor-Matrix by scientists R. Forman and M. Gaudron, they are explored in a whole multitude of scientific papers and separate regulatory legal acts (e.g., in the Kyrgyz Republic). The issues of establishing ecological corridors have been elaborated only in a few studies by landscape ecology and geoecology reps. Based on the analysis of the provisions of the EC RK, the SPNA Law, and other sources of Kazakhstan and foreign law, as well as scientific approaches to the issues of defining and establishing ecological corridors, terminology of landscape ecology and recommendations have been developed to improve Paragraph 22 of Article 1, Paragraphs 1 and 2 of Article 81 of the SPNA Law, as well as to develop new regulatory legal acts.